New and little known feather mites (Acariformes: Astigmata) analysed with low-temperature scanning electron microscopy - Hernandes, Fabio Akashi [UNESP] (2017)
Feather mites (Acari: Astigmata) were analysed with low-temperature scanning electron microscopy, including the description of three new species: Plicatalloptes atrichogynussp. nov. (Analgoidea: Alloptidae) from the Neotropical cormorant Phalacrocorax brasilianus (Gmelin) (Pelecaniformes: Phalacrocoracidae), Metapterodectes saturninussp. nov. (Analgoidea; Proctophyllodidae) from the chalk-browed mockingbird Mimus saturninus (Lichtenstein) (Passeriformes: Mimidae), and Neumannella crypturellasp. nov. (Analgoidea: Dermoglyphidae) from the small-billed tinamou Crypturellus parvirostris (Wagler) (Tinamiformes: Tinamidae). In addition, two previously known species are analysed, Oustaletia pegasus Trouessart, 1855 (Pterolichoidea: Vexillariidae) from the bushy-crested hornbill Anorrhinus galeritus (Temminck) (Bucerotiformes: Bucerotidae), and Opisthocomacarus umbellifer (Trouessart, 1899) (Pterolichoidea: Pterolichidae) from the hoatzin Opisthocomus hoazin (Muller) (Opisthocomiformes: Opisthocomidae). The latter two mite species display a rich variety of setal structures. Alloptes umbrettae Gaud, 1960 (Analgoidea: Alloptidae), known from Scopus umbretta Gmelin (Pelecaniformes: Scopidae), is transferred from the genus Alloptes Canestrini to Plicatalloptes Dubinin and given a new valid name, Plicatalloptes umbrettae (Gaud, 1960) comb. nov.http://zoobank.org/urn:lsid:zoobank.org:pub:5866FF00-1206-4551-9544-8A002ADF7626